Facile synthesis of β-lactoglobulin capped Ag2S quantum dots for in vivo imaging in the second near-infrared biological window. Issue 37 (14th September 2016) - Chen, Jun; Kong, Yifei; Wo, Yan; Fang, Hongwei; Li, Yunxia; Zhang, Tao; Dong, Yu; Ge, Yunsheng; Wu, Ziying; Zhou, Dejian; Chen, Shiyi
Abstract : Effective in vivo fluorescence imaging based on β-LG-Ag2 S quantum dots at the second near-infrared region. Abstract : Effective in vivo fluorescence imaging for cancer screening and diagnostics requires bright and biocompatible fluorophores whose emission can effectively penetrate biological tissues. Recent studies have confirmed that the second near-infrared window (NIR-II, 1000–1400 nm) is the most sensitive spectral range for in vivo imaging due to ultralow tissue absorption and autofluorescence. We report herein a facile synthesis of Ag2 S quantum dots (QDs) that emit at ∼1100 nm using β-lactoglobulin (β-LG) as a biological template. The β-LG protein coating improves water-solubility, faciliates rapid biodistribution and reduces in vivo toxicity of the QDs. Compared to other currently used NIR emitters, β-LG capped Ag2 S QDs exhibit superior photostability and biocompatibility, making them promising probes for in vivo NIR-II imaging.